IMPROVING THE RELIABILITY OF UNDERGROUND METAL AND CONCRETE PIPES - Beliavskyi, Yu. V.; Mashytun, O. V. (Science and Transport Progress, 2005)
The analysis of work of the system «high filling – water-carrying pipe – the base» reveals the causes of stretch deformation alone the pipe axis, deflection of the pipe body in relation to its heads, etc. For solution of these problems new designs of water-carrying pipes have been suggested.